Controlled generation and detection of a thermal bias in Corbino devices under the quantum Hall regime - Real, M. A. (2023)
We present an experimental technique to generate and measure a temperature bias in the quantum Hall effect of GaAs/AlGaAs Corbino samples. The bias is generated by injecting an electric current at a central resistive heater, and the resulting radial temperature drop is determined by conductance measurements at internal and external concentric rings. The experimental results agree with the predictions of numerical simulations of the heat flow through the substrate. We also compare these results with previous predictions based on the thermoelectric response of these devices.